A prospective study of direct medical costs in a large cohort of consecutively enrolled patients with refractory epilepsy in Italy1. (4th June 2015) - Luoni, Chiara; Canevini, Maria Paola; Capovilla, Giuseppe; De Sarro, Giovambattista; Galimberti, Carlo Andrea; Gatti, Giuliana; Guerrini, Renzo; La Neve, Angela; Mazzucchelli, Iolanda; Rosati, Eleonora; Specchio, Luigi Maria; Striano, Salvatore; et al.
Summary Objective To evaluate direct medical costs and their predictors in patients with refractory epilepsy enrolled into the SOPHIE study (Study of Outcomes of PHarmacoresistance In Epilepsy) in Italy. Methods Adults and children with refractory epilepsy were enrolled consecutively at 11 tertiary referral centers and followed for 18 months. At entry, all subjects underwent a structured interview and a medical examination, and were asked to keep records of diagnostic examinations, laboratory tests, specialist consultations, treatments, hospital admissions, and day‐hospital days during follow‐up. Study visits included assessments every 6 months of seizure frequency, health‐related quality of life (Quality of Life in Epilepsy Inventory 31), medication‐related adverse events (Adverse Event Profile) and mood state (Beck Depression Inventory‐II). Cost items were priced by applying Italian tariffs. Cost estimates were adjusted to 2013 values. Results Of 1, 124 enrolled individuals, 1, 040 completed follow‐up. Average annual cost per patient was € 4, 677. The highest cost was for antiepileptic drug (AED) treatment (50%), followed by hospital admissions (29% of overall costs). AED polytherapy, seizure frequency during follow‐up, grade III pharmacoresistance, medical and psychiatric comorbidities, and occurrence of status epilepticus during follow‐up were identified as significant predictors of higher costs. Age between 6 and 11 years, and genetic (idiopathic) generalized epilepsies were associated with the lowest costs. Costs showed prominent variation across centers, largely due to differences in the clinical characteristics of cohorts enrolled at each center and the prescribing of second‐generation AEDs. Individual outliers associated with high costs related to hospital admissions had a major influence on costs in many centers. Significance Refractory epilepsy is associated with high costs that affect individuals and society. Costs differ across centers in relation to the characteristics of patients and the extent of use of more expensive, second‐generation AEDs. Epilepsy‐specific costs cannot be easily differentiated from costs related to comorbidities.